2020
DOI: 10.1177/1355819620963500
|View full text |Cite
|
Sign up to set email alerts
|

Does prevention-focused integration lead to the triple aim? An evaluation of two new care models in England

Abstract: Objectives To examine the effectiveness of two integrated care models (‘vanguards’) in Salford and South Somerset in England, United Kingdom, in relation to patient experience, health outcomes and costs of care (the ‘triple aim’). Methods We used difference-in-differences analysis combined with propensity score weighting to compare the two care model sites with control (‘usual care’) areas in the rest of England. We estimated combined and separate annual effects in the three years following introduction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…33 Previous studies on changes in costs due to integrated care in the community have shown inconsistent results. [34][35][36] This study revealed cost savings through the pilot project, which can be explained based on the results of length of home stay.…”
Section: Discussionmentioning
confidence: 77%
“…33 Previous studies on changes in costs due to integrated care in the community have shown inconsistent results. [34][35][36] This study revealed cost savings through the pilot project, which can be explained based on the results of length of home stay.…”
Section: Discussionmentioning
confidence: 77%
“…The study reported here followed earlier qualitative analysis by some of the same authors at two vertical integration locations in England and one in Wales. 6,7 A quantitative evaluation of new models of care integration at two locations by Stokes and colleagues, 24 includes one location that part way through the period studied also introduced vertical integration but analyses changes commencing at an earlier date and does not separately identify the impact of vertical integration.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…While recent initiatives have begun with a range of objectives including improving patient and carer experiences, policy and system objectives have tended to narrow over time leading to a strong emphasis on reductions in emergency admissions [15][16][17][18][19]. To date, however, there has been little evidence of initiatives successfully reducing emergency admissions [20][21][22][23][24][25][26]. One reason for the lack of evidence is that the initiatives are short-lived and often overlapping.…”
Section: Introductionmentioning
confidence: 99%